Expressive Speech Acts In Toni Morrison’s Novel ‘Blue Eyes’: Psychoanalysis Study - Chairuddin, Chairuddin; Arafah, Burhanuddin; Manugeren, M; Anwar Matondang, Saiful (Universitas Cokroaminoto Palopo, 2025)
This research is to describe the expressive actions and how expressive speech acts describe the psychology of the protagonist, and why expressive actions have a negative impact on the protagonist's psychology in Toni Morrison's Blue Eyes novel. A terrible discrimination in the form of racism and conventional beauty standards against African-American women in America during the 1940s, experienced by the main character Pecola, had a negative impact on her psychology due to being raped by her father and the pressure from her mother's rejection, which further worsened her mental condition, giving her deep trauma so that she lived in her dreams of having blue eyes until she died. The research method used is descriptive qualitative according to W. Webster, which involves describing and categorizing words, phrases, and general ideas in qualitative data. The main data source is a novel supported by books, journals, and electronic news. Data was collected through observation, grouping, and information gathering using pragmatic validity, especially Searle's theory in Yule, and Sigmund Freud's theory with a philosophical approach to help readers understand speech acts as a whole. The significant of this study is to determine expressive acts and how expressive speech acts depict the protagonist's psychology, and why expressive acts have a negative impact on the protagonist's psychology in Toni Morrison's novel Blue Eyes. In this context, the main character uses expressive speech acts in her utterances, which means experiencing psychological states that contain meanings of pleasure, pain, like, dislike, joy, sadness, and apology. The results of this study indicate that expressive speech acts by Pecola are dominated by sadness, dislike, and dreams.